THE ROLE OF COMPUTATIONAL LINGUISTICS IN FOREIGN LANGUAGE LEARNING (The Role of Exact Sciences in the Era of Modern Development, 2025)
In today’s interconnected world, learning foreign languages has become a necessity rather than a luxury. Computational linguistics, which brings together computer science, linguistics, and artificial intelligence, plays an increasingly important role in language education. This paper discusses how computational linguistics supports and enhances foreign language learning by providing innovative tools, adaptive feedback, and personalized learning experiences. It also examines the main benefits and challenges of using computational methods in language education and outlines future prospects for research in this area.